Inflammation, von Willebrand factor, and ADAMTS13 - Chen, Junmei (Blood, 2018)
Increasing evidence indicates that inflammation can cause thrombosis by a von Willebrand factor (VWF)-mediated mechanism that includes endothelial activation, secretion of VWF, assembly of hyperadhesive VWF strings and fibers, cleavage by ADAMTS13, and adhesion and deposition of VWF-platelet thrombi in the vasculature. This mechanism appears to contribute to thrombosis not only in small vessels, but also in large vessels. Inflammation and VWF contribute to atherogenesis and may contribute to arterial and venous thrombosis as well as stroke. Elucidation of the mechanism will hopefully identify new targets and suggest new approaches for prevention and intervention.